Hubungan Status Gizi, Pemberian Asi Eksklusif dan Paparan Asap Rokok Terhadap Kejadian Ispa pada Balita di Puskesmas Sukaraya Kab. OKU - Fauziah Setiawati; Erma Puspita Sari; Siti Aisyah Hamid; Hasbiah Hasbiah (Universitas Batanghari Jambi, 2021)
Acute Respiratory Tract Infection (ARI) is the main cause of morbidity and mortality of children under five in both developed and developing countries. The results of Riskesdas 2018, the prevalence of ARI among children under five in Indonesia is 7.8% and South Sumatra is 8.6%. The prevalence of ARI in Kab.OKU in 2020 14.9% and UPTD Sukaraya Health Center 19.9%. The purpose of this study was to determine the relationship between nutritional status, exclusive breastfeeding and exposure to cigarette smoke simultaneously with the incidence of ARI in children under five at PuskesmasSukarayaKab. OKU 2021. This research is a quantitative study with an analytical survey method using a cross sectional approach. The sample in this study was taken in a non-random with accidental sampling technique. This study uses primary data collected through interview techniques. Data analysis was carried out univariate and bivariate with Chi-Square statistical test. The results of univariate analysis: from 46 samples, 30 (65.2%) suffered from ARI, 16 (34.8%) were not well nourished, 21 (45.7%) were not exclusively breastfed and 17 (37%) were exposed to cigarette smoke. The results of bivariate analysis: there is a significant relationship between nutritional status (p-value 0.008), exclusive breastfeeding (p-value 0.018) and exposure to cigarette smoke (p-value 0.005) simultaneously on the incidence of ARI among children under five at PuskesmasSukarayaKab. OKU 2021. As for suggestions to the leadership and health workers of UPTD PuskesmasSukaraya to increase cross-program and cross-sectoral collaboration in handling ARI, and it is hoped that the community will participate in reducing the incidence of ARI in toddlers by providing nutritious intake, exclusive breastfeeding and clean and healthy living behavior